Ebola virus circulation in Africa: A balance between clinical expression and epidemiological silence - (:unkn) unknown (My University, 2005)
Nearly thirty years after the first epidemics, Ebola virus (EBOV) remains hardly described, its transmission unclear and its reservoir elusive. Soon after the Ebola fever outbreak and virus discovery in 1976 and in order to investigate the distribution of EBOV in Central Africa, several countries including a range of ecological zones were investigated in the early 1980s, using extensive survey: Central African Republic (CAR), Cameroon, Chad, Congo, Gabon and Equatorial Guinea. Since 1992, ELISA antibody test along with a RT-PCR have been used to detect specific virus antibodies and characterize viral RNA. The widely separated geographic locations of outbreaks have suggested that the reservoir and the transmission cycle of EBOV are probably closely associated with the rain forest ecosystem, what is supported by the distribution of antibodies. The fact that outbreaks seldom occur suggests the presence of a rare or ecologically isolated animal reservoir having few contacts with humans and non-human primates. However various serological investigations showed a high prevalence in humans without any pathology reported. This suggests a circulation of both pathogenic and non-pathogenic strains as well as more frequent contacts with man than expected, and could partially explain fifteen years of Ebola fever silence between the emergence and re-emergence of Ebola virus in the Congolese basin. Nowadays, largely enlightened by the study of recent epizootic and epidemic manifestations of EBOV in Gabon and neighboring countries, EBOV natural history starts to be understood as for the fundamentals of epizootic in non-human primates and chains of transmission.
Keywords: African Research